INTEGRASI MANAJEMEN WAKTU KONTEMPORER DAN PERANGKAT ARTIFICAL INTELLIGENCE (AI) DALAM MENINGKATKAN EFEKTIVITAS BELAJAR MAHASISWA: SEBUAH TINJAUAN PUSTAKA - Filna Zilma Alidai; Mardiyah; Sabilul Fathon; Farendra Dwi; M. Alif Hubbil (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2026)
The shifting landscape of higher educationn in the digital era demands students not only master conventional time management but also to adapt to technology utilization. However, many prior studies still focus on manual time management and overlook the role of smart technology, leaving a gap in the literature regarding how modern technology can be integrated. This library research aims to examine the integration of contempory time management and artifical intelligence (AI) tools in enhancing student learning effectiveness. The method employed is library research, analyzing reputable scientific articles, books, and indexed academic documents from 2020 to 2026. The result indicate that conventional time management such as priority matrices and scheduling is transforming into a more efficient practice trough virtual assistant and AI based applications. AI tools contribute significantly by automatically breaking down complex tasks, minimizing procrastination, and generating dynamic priority scales. Nevertheless, this implementation must be balanced with critical awareness of personal data security. This study concludes that the synergy between individual disclipline and wise AI utilization fosters a more responsive time management model that directly optimizes students’ learning effectiveness.